1997
DOI: 10.1093/hmg/6.2.277
|View full text |Cite
|
Sign up to set email alerts
|

P53 Activates Fanconi Anemia Group C Gene Expression

Abstract: The tumor suppressor protein p53 (wtp53) can bind to specific target sequences and activate transcription of genes adjacent to these DNA elements. Two p53 binding sites are present in the gene coding for the Fanconi anemia complementation group C (FAC), one in the promoter region (from -1295 to -1266) and one in the coding region of FAC (from +1828 to +1848). Gel shift experiments show that wtp53 binds to the p53 target sequence in the promoter region of the FAC gene. We have investigated whether binding of p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Promoter analyses for mutations and the methylation status of FA genes have been well characterized; these statuses are known to affect the FA/BRCA pathway (Taniguchi et al 2003). Among FA genes, the promoter of FANCC has been cloned and shown to be regulated by p53 (Savoia et al 1995; Liebetrau et al 1997). Once functional links between the E2F1 and FA/BRCA pathways have been established, the complete system biology of the FA/BRCA pathway could be analyzed by examining their promoter regulation by cell cycle-associated key transcriptional regulators, including p53.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter analyses for mutations and the methylation status of FA genes have been well characterized; these statuses are known to affect the FA/BRCA pathway (Taniguchi et al 2003). Among FA genes, the promoter of FANCC has been cloned and shown to be regulated by p53 (Savoia et al 1995; Liebetrau et al 1997). Once functional links between the E2F1 and FA/BRCA pathways have been established, the complete system biology of the FA/BRCA pathway could be analyzed by examining their promoter regulation by cell cycle-associated key transcriptional regulators, including p53.…”
Section: Discussionmentioning
confidence: 99%
“…Early work from the Hoehn group showed that oxidative stress altered p53 expression and function in cultured FA cells [100-102]. Recently, studies from several other groups demonstrated that Fancd1 -/- , Fancd2 -/- and Fancc -/- mice have accelerated tumor development in a Trp53 -deficient background [103-105], and that p53 knockdown in FANCD2-deficient zebrafish leads to increased apoptosis and developmental defects [106].…”
Section: Fanconi Anemia and Oxidative Dna Damagementioning
confidence: 99%
“…The establishment of p53 contribution to the expression of FAC was based on the description of two p53‐binding sites in the promoter and coding region of the gene, respectively. Also, p53 overexpression led to significant enhancement of transcription of FAC gene, although luciferase assays disclosed no modulation of the promoter activity (leading to the conclusion that p53‐binding is not directly responsible for activation of FAC transcription) [94].…”
Section: Transcriptional Modifications Of Dna Repair By Upsmentioning
confidence: 99%